FAMILY SUPPORTIVE SUPERVISOR BEHAVIOR SEBAGAI PEMODERASI PENGARUH WORK LIFE BALANCE TERHADAP JOB SATISFACTION DI MASA PANDEMI COVID-19 PADA KARYAWAN PERUSAHAAN EKSPEDISI DI KOTA BENGKULU - Rahma Fitria Ningsih; Sugeng Susetyo (Management Insight: Jurnal Ilmiah Manajemen, 2022)
The purpose of this study was to determine whether family supportive supervisor behavior can moderate the effect of work life balance on job satisfaction during the COVID-19 pandemic for employees of shipping companies in Bengkulu City. This study uses a quantitative approach by using primary data obtained through questionnaires and secondary data obtained through the internet. The sample is 111 employees at PT. Pos Indonesia (Persero) Bengkulu City and 105 employees at PT. Tiki Jallur Nugraha Ekakurir (JNE) Bengkulu City using simple random sampling method. The data processing technique of this research uses the Statistical Package For Social Science (SPSS) software version 22.0. The analytical method used by the researcher is hypothesis testing and Moderated Regression Analysis (MRA). The results of this study; 1) Work life balance has a positive and significant effect on job satisfaction. 2) Family supportive supervisor has a positive and significant effect on job satisfaction. 3) Family supportive supervisors cannot moderate the effect of work life balance on job satisfaction.